2018
DOI: 10.3390/su10124530
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Trends of Ambient Ozone and Nitrogen Oxides at Urban, Suburban, and Rural Sites from 2011 to 2017 in Shenzhen, China

Abstract: The emissions of nitrogen oxides (NOx) decreased under China’s air quality control policies. However, concern remains regarding the response of ozone (O3) in the metropolitan areas. The characteristics and trends of ambient O3 and NOx in Shenzhen were investigated during the 2011–2017 period. Both the human population and vegetation are exposed to higher O3 at suburban and rural sites than at the urban site. The O3 weekend effect is significant (p = 0.062) at the urban site, with O3 levels 1.19 ppb higher on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 53 publications
3
14
1
Order By: Relevance
“…9), with a higher correlation coefficient between background and suburban sites (R = 0.8). As for the regression fits, suburban values are closer to the background concentrations for O 3 , consistent with the findings in previous studies (Tong et al, 2017;Huang et al, 2018). We further calculate the Δ[MDA8] and Δ[PM 2.5 ] for summer (JJA) and winter (November-December, ND) between urban and background sites in 2017.…”
Section: Comparison Of Air Pollutants Over Urban Suburban and Backgrsupporting
confidence: 87%
See 2 more Smart Citations
“…9), with a higher correlation coefficient between background and suburban sites (R = 0.8). As for the regression fits, suburban values are closer to the background concentrations for O 3 , consistent with the findings in previous studies (Tong et al, 2017;Huang et al, 2018). We further calculate the Δ[MDA8] and Δ[PM 2.5 ] for summer (JJA) and winter (November-December, ND) between urban and background sites in 2017.…”
Section: Comparison Of Air Pollutants Over Urban Suburban and Backgrsupporting
confidence: 87%
“…5c), likely because of regionally high emissions of both biogenic and anthropogenic VOCs (Liu et al, 2018) and the substantial NO x reductions (He et al, 2017;Song et al, 2017) transform a VOC-limited regime to a mixed sensitive environment over YRD (Jin and Holloway, 2015) and result in the increase in urban O 3 (Wang et al, 2019). In terms of interannual variation, Huang et al(2018) found that the urban [O 3 ] in Shenzhen, a city in PRD, increased faster than its nonurban counterpart during 2012-17, leading to a decline in the absolute Δ[MDA8]. A similar trend is also present in our analyses for the whole PRD domain during 2015-18 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(www.preprints.org) | NOT PEER-REVIEWED | Posted: 5 October 2018 doi:10.20944/preprints201810.0101.v1NO2 concentrations which may be caused by its large pollution and its location adjacent to the SEZ districts. NO2 levels have been lowered over time, possibly linked to the traffic energy reform in Shenzhen and the national NOx regulation measures[14][15]31]. Meanwhile, O3 concentrations are increasing which are probably caused by lowered NOx titration effects in a VOC limited urban environment.…”
mentioning
confidence: 99%
“…Meanwhile, O3 concentrations are increasing which are probably caused by lowered NOx titration effects in a VOC limited urban environment. Great challenges remain in controlling O3 in Shenzhen[31].The concentrations of all air pollutants in Shenzhen have met current national annual target values. The thresholds for PM and O3 of national air quality standard are inherited from WHO's interim target-1 (IT1).…”
mentioning
confidence: 99%